2019
DOI: 10.1007/s00330-019-06116-9
|View full text |Cite
|
Sign up to set email alerts
|

Objective and subjective comparison of virtual monoenergetic vs. polychromatic images in patients with pancreatic ductal adenocarcinoma

Abstract: Objectives The aim of this study was to assess the objective and subjective image characteristics of monoenergetic images (MEI[+]), using a noise-optimized algorithm at different kiloelectron volts (keV) compared to polyenergetic images (PEI), in patients with pancreatic ductal adenocarcinoma (PDAC). Methods This retrospective, institutional review board-approved study included 45 patients (18 male, 27 female; mean age 66 years; range, 42–96 years) with PDAC who had und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 24 publications
(33 reference statements)
4
36
0
Order By: Relevance
“…Recently, a noise-optimized MEI (+) reconstruction algorithm was developed to perform spatial frequency-based recombination, which results in the highest possible image contrast by reducing the image noise at lower energy levels. 32 In our study, image noise was increased in the 40 keV MEI (+) 300 group compared with that of the CTA 370 group, which is consistent with previous results. 16 However, subjectively, there was no statistically significant or clinical difference in the perceived image noise between the 2 groups, especially in the evaluation of the arteries.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, a noise-optimized MEI (+) reconstruction algorithm was developed to perform spatial frequency-based recombination, which results in the highest possible image contrast by reducing the image noise at lower energy levels. 32 In our study, image noise was increased in the 40 keV MEI (+) 300 group compared with that of the CTA 370 group, which is consistent with previous results. 16 However, subjectively, there was no statistically significant or clinical difference in the perceived image noise between the 2 groups, especially in the evaluation of the arteries.…”
Section: Discussionsupporting
confidence: 92%
“…However, the conventional HRCT and U-HRCT images were acquired almost at the same time, so that there was no difference in the quality of the cadaveric lungs between conventional HRCT and U-HRCT. A method to evaluate image quality by measuring tumor SNR has been reported [21], but SNR was not measured in this study. Because some evaluation items were not uniform (such as honeycombing, reticulation, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The two image sets were used for modified line-density analysis [24]. The tumor was identified on 80/Sn150 images, and one reader, with 4 years of experience, positioned a line of 10 mm in length and 2 mm in width perpendicular to the tumor margins with one half of the line within the tumor and the other half within the normal tissue.…”
Section: Plos Onementioning
confidence: 99%
“…In other words, low kVp/high kVp with tin filter (Sn) CT generates low kVp, virtual noncontrast, and blended images, which are widely used in oncology [14]. In addition, virtual monochromatic images can be used to magnify the iodine contrast-to-noise ratio (CNR) to enhance the differentiation between tumor and background using DECT in oncology [15,16]. Although initial DECT revealed a three times higher radiation dose than single-energy CT [17], recent studies have demonstrated that third-generation dual-source DECTs can be performed without a radiation dose penalty or impairment of image quality compared to single-energy CT with 100-120 kVp [18,19].…”
Section: Introductionmentioning
confidence: 99%